ANALYSIS OF THE MAIN DETERMINANTS OF THE RUSSIAN CONSUMERS’ CURRENT MOOD - I. Yu. Aleksandrova (Вестник университета, 2020)
The socio-psychological phenomenon “consumer mood”, which is interpreted as an emotional and evaluative summary of the subjective understanding of the individual of various information elements that form the semantic structure of his implicit theory of consumption, has been investigated. A hypothesis has been put forward that the formation of the semantic field of the implicit theory of consumption of an individual is based on two system-forming factors: 1) the real purchasing power of the consumer, 2) the dynamics of his socio-economic status. In the event that both factors have negative actual indicators, the mood of consumer will be characterized by a negative emotional tone and high stability over time. The proposed hypothesis is confirmed by the revealing and analysis of the main determinants of the current mood of Russian consumers, and their subsequent comparison with the consumer sentiment index, identificated empirically.